Fleksibilitas Siswa Sekolah Dasar - Andhega Wijaya (Universitas Pendidikan Indonesia (UPI), 2020)
Abstract This study aims to determine the flexibility profile of children aged 7-12 years. Descriptive approach is used in this study with the number of samples involved as many as 20 students per class with as many as 6 classes in accordance with their respective class levels. The instrument used in this study was a flexiometer, to determine the student's flexibility or flexibility. Data analysis was performed using statistical descriptive techniques. The results showed that for men shoulder flexibility at 7 years (6.12), at 8 years (6.08), at 9 years (5.19), at 10 years (5.84), at 11 years old (5,77) at 12 years old (5,89). Men Wrist at the age of 7 years (1.47), at the age of 8 years (1.47), at the age of 9 years (1.42), at the age of 10 years (1.41), at the age of 11 years ( 1,4), and at the age of 12 years (1,4). For Strike men at 7 years (1.06), at 8 years (0.99), at 9 years (0.992), at 10 years (0.98), at 11 years (0, 1), and at the age of 12 years (0.11). For women togok at 7 years (0.97), at 8 years (0.92), at 9 years (0.94), at 10 years (0.96), at 11 years (0, 99), and at the age of 12 years (1.06). Researchers concluded that the data from this profile can be used as a reference for educators, parents, or the surrounding community to be able to prepare these students to perform better in accordance with their flexibility in the field of sports, so they can adjust the sport they want according to the percentage of the flexibility of the students. And research will be better if coupled with profiles of physical fitness elements, such as balance, so that the data will be complete to be able to identify from students who will determine the choice of sports branches. Abstrak Penelitian ini bertujuan untuk mengetahui profil fleksibilitas siswa umur usia 7-12 tahun. Pendekatan Deskriptif digunakan dalam penelitian ini dengan jumlah sampel yang terlibat sebanyak 20 siswa tiap kelasnya dengan sebanyak 6 kelas sesuai dengan tingkat kelasnya masing-masing. Instrumen yang digunakan dalam penelitian ini adalah flexiometer, untuk mengetahui kelenturan atau fleksibilitasnya siswa tersebut. Analisis data dilakukan dengan teknik deskriptif statistik. Hasil penelitian menunjukkan bahwa untuk laki-laki fleksibilitas bahu pada umur 7 tahun (6,12), pada umur 8 tahun (6,08), pada umur 9 tahun (5,19), pada umur 10 tahun (5,84), pada umur 11 tahun (5,77) pada umur 12 tahun (5,89). Laki-laki Pergelangan tangan pada umur 7 tahun (1,47), pada umur 8 tahun (1,47), pada umur 9 tahun (1,42), pada umur 10 tahun (1,41), pada umur 11 tahun (1,4), dan pada umur 12 tahun (1,4). Untuk laki-laki Togok pada umur 7 tahun (1,06), pada umur 8 tahun (0,99), pada umur 9 tahun (0,992), pada umur 10 tahun (0,98), pada umur 11 tahun (0,1), dan pada umur 12 tahun (0,11). Untuk perempuan togok pada umur 7 tahun (0,97), pada umur 8 tahun (0,92), pada umur 9 tahun (0,94), pada umur 10 tahun (0,96), pada umur 11 tahun (0,99), dan pada umur 12 tahun (1,06). Peneliti menyimpulkan bahwa data dari profil ini bisa dijadikan rujukan bagi para pendidik, orang tua, ataupun masyarakat sekitar untuk bisa menyipakan siswa didik tersebut bisa bertampil lebih baik sesuai dengan kelenturannya di bidang olahraga, sehingga mereka bisa menyesuiakan cabang olahraga yang mereka inginkan sesuai dengan prosentas dari kelenturan siswa didik tersebut. Dan penelitian akan lebih baik bila ditambah dengan profil dari unsur-unsur kebugran jasmani, misal keseimbangan, sehingga data akan lengkap untuk bisa mengidentifikasi dari siswa didik yang akan meenntukan pilihan dari cabang olahraganya.